Membentuk Madrasah Diniyah sebagai Alternatif Lembaga Pendidikan Elite Muslim bagi Masyarakat - Zulfia Hanum Alfi Syahr (MODELING: Jurnal Program Studi PGMI, 2017)
Diniyaa Madrasaa as a non-formal educational institutions based on religious activities which are carried out at evening after formal school hours. Diniyaa Madrasaa’s simple curriculum and short period learning activity is not being a barrier for producing educated and intellectual students. Thus, the existence of Diniyaa Madrasaa can be developed into one of the moslem elite schools that can accomodate the education needed of lower middle class people because the tuition fee is cheap. Diniyaa Madrasaa also able to compete with other moslem elite school that has more expensive tuition fees. Therefore, now in the era of modernization, the manager of Diniyaa Madrasaa should avoid the temptation of material and secularism curricullum in the education activity. The purpose is to create the smart young moslem generation in knowledge and faith.